ENVIRONMENTAL BY GENOTYPE INTERACTIONS AND THEIR EFFECTS ON GROWTH RATE OF AWASSI SHEEP REARED IN SEMI-ARID REGION - Al-Amareen, Ahmad; Jawasreh, Khaleel; Awabdeh, Sami; Al-Barznji, Yousif; AlBreiki, Mohammad; Alshdaifat, Mustafa; Araishi, Mohamad; Sherydeh, Mowafaq; Sweidan, Rawad; Aloueedat, Mohammad; Hijazi, Jomana; Alharbeed, Leqaa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Due to its reputation for receiving little rainfall, Jordan’s Al-Mafraq region (where the sheep is reared) is susceptible to droughts and water shortages and poor range. Estimating genetic and environmental factors for growth traits in purebred Awassi sheep in Al Mafraq (semi-arid region) was the goal of the study. The study’s data came from 3481 lambs born at the National Centre for Agricultural Research’s (NARC) Al-Khanasri livestock and rangeland research station in Jordan over a 15-year period (2009–2023). Birth weights (BWT), weaning weights (WWT), and average daily gain from birth to weaning (ADG) were the traits under study. While genetic parameters were estimated assuming the mixed model using the Restricted Maximum Likelihood (REML) method process using the ASReml program, the environmental effects were estimated using the SAS program’s General Linear Model (GLM) technique. BWT, WWT, and ADG were significantly impacted by the year of birth, dam weight at lambing, parity, lamb sex, and method of birth; however, the examined growth traits were not significantly impacted by the dam’s age (P > 0.05). BWT, WWT, and ADG had heritability estimates of 0.38±0.05, 0.21±0.05, and 0.16±0.05, respectively, and corresponding repeatabilities of 0.41±0.05, 0.39±0.06, and 0.32±0.05. Environmental correlations ranged from negative (-0.20) between BWT and ADG to high (0.98) between WWT and ADG, while phenotypic correlations ranged from negative (-0.011) between BWT and ADG to high (0.98) between WWT and ADG. The estimated genetic correlations among the traits under study were high and strongly positive, ranging from 0.54 between BWT and ADG to 0.99 between WWT and ADG. To sum up, the findings ought to be used to a genetic selection program that aims to enhance Awassi sheep’s growth performance.